Perceived stress, emotional intelligence and psychological wellbeing of mental health professionals puring covid-19 in Pakistan - Saralah Devi Mariamdaran Chethiyar; Tania Qamar; Muhammad Ali Equatora (Journal of Advanced Guidance and Counseling, 2022)
AbstractPurpose - The aim of the research was to assess the relationship between perceived stress, emotional intelligence and psychological wellbeing of mental health professionals during Covid-19 in Pakistan.Method - The population of this study is (n=150) mental health professionals (psychologists, psychiatrists, psychiatry nurses). Data was collected through purposive sampling strategy.Result - The results showed that perceived stress has significant negative association with psychological wellbeing, however, emotional intelligence has significant positive association with psychological wellbeing. Regression findings revealed that perceived stress and emotional intelligence were significant predictors of psychological wellbeing among mental health professionals. ANOVA findings showed psychological wellbeing score was high in psychiatrists then other mental health professionals.Implication – This research guided to enhance the emotional intelligence skill. The present study will help to understand the importance of psychological wellbeing especially among mental health professionals.Originality - The present study has great importance for mental health professionals. The results of the current study have suggestions for theories in the field of socialization to understand the perceived stress, emotional intelligence and psychological wellbeing mostly experienced, which increase our knowledge.***Tujuan - Penelitian ini bertujuan untuk menilai hubungan antara stres yang dirasakan, kecerdasan emosional, dan kesejahteraan profesional kesehatan mental selama Covid-19 di Pakistan.Metode - Populasi penelitian ini adalah (n=150) tenaga kesehatan jiwa (psikolog, psikiater, perawat psikiatri). Data dikumpulkan melalui strategi purposive sampling.Hasil - Hasil penelitian menunjukkan bahwa persepsi stres memiliki hubungan negatif yang signifikan dengan kesejahteraan, namun kecerdasan emosional memiliki hubungan positif yang signifikan dengan kesejahteraan. Temuan regresi mengungkapkan bahwa stres yang dirasakan dan kecerdasan emosional merupakan prediktor signifikan kesejahteraan di kalangan profesional kesehatan mental. Temuan ANOVA menunjukkan skor kesejahteraan lebih tinggi pada psikiater daripada profesional kesehatan mental lainnya.Implikasi - Penelitian ini dipandu untuk meningkatkan keterampilan kecerdasan emosional. Studi ini akan membantu untuk memahami pentingnya kesejahteraan, terutama di kalangan profesional kesehatan mental.Originalitas - Penelitian ini sangat penting bagi para profesional kesehatan mental. Hasil penelitian saat ini memiliki saran untuk teori di bidang sosialisasi untuk memahami stres yang dirasakan, kecerdasan emosional, dan kesejahteraan sebagian besar dialami, yang meningkatkan pengetahuan kita.